THE EFFECT OF PSYCHOTROPIC DRUGS ON WEIGHT IN ELDERLY INPATIENTS AT NATIONAL GERIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Psychotropic drugs, including antipsychotics and antidepressants, have been found to have a significant weight-gaining effect.Objectives: To evaluate the impact of several psychotropic drugs on the weight of elderly patients with mental disorders inpatients at the Department of Mental Health, National Geriatric Hospital.Method: A descriptive, prospective study was conducted, including 31 inpatients at the Department of Mental Health, National Geriatric Hospital from April 2019 to January 2020. Anthropometric measurements were taken at admission, after 1 week, after 2 weeks, after 3 weeks, and after 4 weeks.Results: The most frequently used drugs included antidepressants such as mirtazapine (51.6%) and paroxetine (22.6%). Antipsychotic drugs such as sulpiride (38.7%), quetiapine (25.8%), olanzapine (22.6%), and risperidone (16.1%) were used. The majority of patients gained less than 7% of their body weight after treatment; no patients gained more than 7% of their body weight during treatment. After two weeks, the patients' weight increased significantly, with an average increase of 0.97 kg (SD=0.8; p=0.001). Follow-up after 2 weeks showed a significant reduction in the number and proportion of patients experiencing appetite problems.Conclusion: Elderly patients using antipsychotic drugs showed significant improvement in appetite and weight gain.
Keywords: elderly, psychotropic drugs, antidepressants, antipsychotics, weight-gain.